The Fundamentalist Graduation of Moral Rights between those who Prove and Deny them (Islamic Sciences Journal, 2023)
The development of the world has raised many financial problems, including moral rights "innovation rights". The views of contemporary jurists have been inconsistent with regard to the creator's financial right.The study has found that the sources of doctrinal jurisprudence played a major role in this dispute and highlighted it more fundamentally than the previous studies that dealt with the topic on his part in both legal and jurisprudential ones. The study has also shown the sources of Islamic law in the weighting of the opinion of proving the financial right of the innovators, and the reference to the impact of this dispute on the behavior of the innovation.